2023
DOI: 10.1021/acsanm.3c01591
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Porous ZnO|Metal Complex Nanostructured Materials: Application to Electrocatalytic CO2 Reduction

Abstract: We developed a simple and versatile approach for the electrochemical growth of hybrid ZnO|molecular catalyst nanostructured layers. Metal oxide|catalyst hybrid nanoporous layers with a sponge-like structure at the nanoscale and multiscale three-dimensional (3D) hierarchical structures based on nanoporous zinc oxide (ZnO) layers grown on ZnO nanorods were obtained. The thickness and structure of the hybrid nanoporous layers as well as the catalyst concentration can be tuned. This method allows the introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
(113 reference statements)
1
4
0
Order By: Relevance
“…As shown in Figure a, the diffraction peaks detected at 2θ = 31.8, 34.4, 36.2, 47.5, 56.6, 62.9, and 68.0° correspond to the (100), (002), (101), (102), (110), (103) and (112) planes of ZnO, respectively . It can be observed that the positions of the diffraction peaks for all three samples were in precise accordance with the standard card of hexagonal wurtzite ZnO (JCPDS 36-1451) . No other impurity peaks were detected, demonstrating the high purity of the synthesized samples.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…As shown in Figure a, the diffraction peaks detected at 2θ = 31.8, 34.4, 36.2, 47.5, 56.6, 62.9, and 68.0° correspond to the (100), (002), (101), (102), (110), (103) and (112) planes of ZnO, respectively . It can be observed that the positions of the diffraction peaks for all three samples were in precise accordance with the standard card of hexagonal wurtzite ZnO (JCPDS 36-1451) . No other impurity peaks were detected, demonstrating the high purity of the synthesized samples.…”
Section: Resultssupporting
confidence: 55%
“…34 It can be observed that the positions of the diffraction peaks for all three samples were in precise accordance with the standard card of hexagonal wurtzite ZnO (JCPDS 36-1451). 40 No other impurity peaks were detected, demonstrating the high purity of the synthesized samples. The average crystallite sizes of the three samples were calculated by the Debye−Scherrer formula (D = 0.9 λ/β cos θ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A water-soluble tetracationic Co phthalocyanine complex (Figure S3) was encapsulated into the nanoporous ZnO layer during its photoelectrodeposition on the ZnO:Al window layer of the CIGS solar cells. The thickness of the ZnO|CoPcTA nanoporous (ZnO|CoPcTA NP) layer and the concentration of the catalyst could be controlled by adjusting the transferred charge during the ZnO growth process, as observed in Figure a . Increasing the charge from 0 to 4 C cm –2 results in a relatively linear increase in the ZnO|CoPcTA NP thickness up to 1200 nm.…”
mentioning
confidence: 99%
“…To investigate the CO 2 reduction activity of the modified CIGS device under PEC conditions, linear sweep voltammetry (LSV) experiments were performed under chopped AM 1.5G illumination in a 0.1 M TBAPF 6 acetonitrile solution with 1% and 2% water as proton sources, saturated with either Ar or CO 2 (Figure a). The addition of a proton source was found to enhance the catalytic performance of the ZnO|CoPcTA NP layers, most likely by accelerating CO 2 protonation and C–O bond cleavage along with the overall reaction CO 2 + normalH 2 normalO + 2 normale CO + 2 OH …”
mentioning
confidence: 99%